Crystallization and preliminary x-ray characterization of a lectin from Cicer arietinum (chickpea) - Katre, Uma V.; Gaikwad, S. M.; Bhagyawant, S. S.; Deshpande, U. D.; Khan, Mohammad Islam; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Extracellular biosynthesis of bimetallic Au-Ag alloy nanoparticles - Senapati, S.; Ahmad, Absar; Khan, Mohammad Islam; Sastry, M.; Kumar, R. (Small, 2005)
Keywords: alloys; Biosynthesis; composites; enzymes; Nanoparticles

Extra-/intracellular biosynthesis of gold nanoparticles by an alkalotolerant fungus, trichothecium sp. - Ahmad, Absar; Senapati, Satyajyoti; Khan, Mohammad Islam; Kumar, Rajiv; Sastry, Murali (Journal of Biomedical Nanotechnology, 2005)
The development of reliable, eco-friendly processes for the synthesis of nanoscale materials is an important aspect of nanotechnology. As part of our ongoing investigation into the use of fungi for nanoparticle synthesis, we report herein that depending on the reaction conditions of the fungus Trichothecium sp. with aqueous gold ions, gold nanoparticle synthesis can be controlled to occur either within the biomass or extracellularly. Moreover, we have found that reaction of gold ions with the Trichothecium sp. fungal biomass under stationary conditions results in the rapid extracellular formation of gold nanoparticles of spherical, rod-like and triangular morphology whereas reaction of the biomass under shaking conditions resulted in intracellular growth of the nanoparticles. It is believed that on changing the reaction conditions of the fungus with gold ions, the enzymes and proteins which are being released into the medium under stationary conditions do not get released under shaking conditions resulting in the formation of extracellular or intracellular gold nanoparticles respectively. The gold nanoparticles are not toxic to the cells and the cells continued to grow after the biosynthesis of the gold nanoparticles in both the cases.
Keywords: Biosynthesis; enzymes; Fungus; Gold; Morphology Control; Nanoparticles

Beta-lactam-azasugar hybrid as a competitive potent galactosidase inhibitor - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M.; Puranik, Vedavati G. (Tetrahedron Letters, 2006)
A beta-lactam-azasugar hybrid (polyhydroxylated carbacephem) has been designed and synthesized as a potent glycosidase inhibitor. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: beta-Galactosidase; beta-lactam-azasugar; glycosidase inhibitor; hybrid molecules

Binding of T-antigen disaccharides to artocarpus hirsuta lectin and jacalin are energetically different - Gaikwad, Sushama M.; Khan, Mohammad Islam (Photochemistry and Photobiology, 2006)
The thermodynamics of binding of Me-alpha-GalNAc, Gal-beta-1-3GalNAc-alpha-O-Me (T-antigen-alpha), Gal-beta-1-3GalNAc and Gal-alpha-1-6Glc (mellibiose) to Artocarpus hirsuta lectin was studied using fluorescence spectroscopy. The binding affinities of the saccharides are in the order Gal-beta-1-3GalNAc-alpha-O-Me > Me-alpha-GalNAc > Me-alpha-Gal > Gal-beta-1-3GalNAc > Gal-alpha-1-6Glc. The binding affinities were comparable to those for jacalin. However, binding of the saccharides to the A. hirsuta lectin was not affected as strongly by temperature as observed in jacalin and the trend was found to be reversed. Values for Delta H and Delta S were found to be positive in A. hirsuta lectin-disaccharide binding despite similar binding affinities. Thus, with 99% structural and 96% sequence homology, with similar sugar specificity and affinity, the energetics of the disaccharide binding of the two lectins seem to be different. Me-alpha-GalNAc binding to A. hirsuta lectin is enthalpically driven, because the association constant decreases with increasing temperature. However, the binding of the T-antigen disaccharides and mellibiose disaccharides to the lectin is entropically driven. The difference in the molecular associations in the packing and variation of the C-terminal length of the P chain of the A. hirsuta lectin could be reflected in the different disaccharide binding energetics.

Convergent approach toward the synthesis of the stereoisomers of C-6 homologues of 1-deoxynojirimycin and their analogues: evaluation as specific glycosidase inhibitors - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M. (Journal of Organic Chemistry, 2006)
A new and stereoselective strategy is developed to synthesize an appropriate template 9 to obtain C-6 homologues of 1-deoxyazasugars such as 1-deoxy-D-galactohomonojirimycin ( 5), 1-deoxy-4-hydroxymethyl-D-glucohomonojirimycin (6), and their enantiomers. The template 9 is also used to obtain neutral nonbasic pseudo-glyconolactam (8), C-4 amino, and methyl analogues of 1-deoxy- homonojirimycin as new analogues of 1- deoxyhomoazasugars. Compound 5 is found to be a potent and specific inhibitor to alpha-galactosidase (K-i = 1.7 mu M). Similarly compounds 6 (K-i = 28 mu M), ent-5 (K-i = 129 mu M), and ent-6 K-i = 12 mu M) exhibited specific inhibition of beta-glucosidase.

Purification, characterization and substrate specificity of thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) - Gote, M. M.; Khan, Mohammad Islam; Gokhale, D. V.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar (Process Biochemistry, 2006)
An extracellular thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) has been purified to homogeneity by chromatographic step, using Phenyl Sepharose CL-4B column. The specific activity of the enzyme was increased approximately 389-fold, from 1.03 U/mg protein to 400 U/mg protein. The molecular mass of the purified enzyme as determined by SDS-PAGE and gel filtration was 79.9 and 165.9 kDa, respectively, suggesting dimeric nature. The purified alpha-galactosidase is a non-glycosylated protein with a pI of 4.9. The pH and temperature optima for the purified enzyme are 6.5-7.0 and 65 degrees C, respectively. The alpha-galactosidase is stable over a broad pH range (3-9) and its half-life of inactivation (t(1/2)) at 70 degrees C is 30 min. The partial N-terminal sequence of alpha-galactosidase showed remarkable homology (80% similarity) with earlier reported alpha-galactosidase from B. stearothermophilus NUB 3621. The secondary structure of the enzyme determined by circular dichroism (CD) spectroscopy exhibited alpha/beta class of protein and showed temperature induced conformational forms below and above the transition temperature. The purified enzyme showed biphasic Arrhenius plot with break point at 55 degrees C for pNPG and 50 degrees C for melibiose, raffinose and stachyose. The enzyme hydrolyzes alpha-1-3, alpha-1-4, and alpha-1-6 galactosidic linkages and not the beta-galactosidic linkages. Synthetic substrates pNPG and oNPG had lower K-m and higher K-cat as compare to natural substrates, melibiose, raffinose, and stachyose. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha-galactosidase; Bacillus stearothermophilus (NCIM-5146); Purification; Secondary structure; thermostable enzyme

Active site directed chemical modification of alpha-galactosidase from bacillus stearothermophilus (NCIM 5146): involvement of lysine, tryptophan and carboxylate residues in catalytic site - Gote, M. M.; Khan, Mohammad Islam; Khire, Jayant Malhar (Enzyme and Microbial Technology, 2007)
The catalytic amino acid residues of the extracellular a-galactosidase (alpha-D-galactoside galactohydrolase; EC 3.2.1.22) from Bacillus stearothermophilus NCIM 5146 were investigated by pH dependence and chemical modification studies. These results suggested that carboxylate and a lysine residue take part in catalysis and only lysine residues were essential for substrate binding. Carbodiimide mediated chemical modification of the enzyme also supported that a carboxylate residue located in the active site act as a nucleophile base in substrate cleavage. Acylation and reductive methylation of lysine residues by acetic, citraconic anhydride and sodium borohydride suggested that four protonated lysine residues carrying positive charge on its epsilon-amino group provides the positive charge density for binding of the substrate. Additionally four tryptophan residues also found near to the active site and in a moderately hydrophobic environment. Kinetic and thermal inactivation study of modified enzyme indicated that these tryptophan residues might have a role in the catalytic site as well as in the thermal stabilization of active site conformation at higher temperature. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Active site; alpha-galactosidase; Bacillus stearothermophilus; carboxylate; Chemical modification; lysine; Tryptophan

All-solid-state' electrochemistry of a protein-confined polymer electrolyte film - Parthasarathy, Meera; Pillai, Vijayamohanan K.; Mulla, Imtiaz S.; Shabab, Mohammed; Khan, Mohammad Islam (Biochemical and Biophysical Research Communications, 2007)
Interfacial redox behavior of a heme protein (hemoglobin) confined in a solid polymer electrolyte membrane, Nafion (a perfluoro sulfonic acid ionomer) is investigated using a unique `all-solid-state' electrochemical methodology. The supple phase-separated structure of the polymer electrolyte membrane, with hydrophilic pools containing solvated protons and water molecules, is found to preserve the incorporated protein in its active form even in the solid-state, using UV-visible, Fluorescence (of Tryptophan and Tyrosine residues) and DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy. More specifically, solid-state cyclic voltammetry and electrochemical impedance of the protein-incorporated polymer films reveal that the Fe2+-form of the entrapped protein is found to bind molecular oxygen more strongly than the native protein. In the `all-solid-state' methodology, as there is no need to dip the protein-modified electrode in a liquid electrolyte (like the conventional electrochemical methods), it offers an easier means to study a number of proteins in a variety of polymer matrices (even biomimetic assemblies). In addition, the results of the present investigation could find interesting application in a variety of research disciplines, in addition to its fundamental scientific interest, including protein biotechnology, pharmaceutical and biomimetic chemistry. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: all-solid-state; cyclic voltammetry; hemoglobin; Impedance; Nafion; redox behavior

CdS quantum dots: enzyme mediated in vitro synthesis, characterization and conjugation with plant lectins - Ansary, Abu Ayoobul; Kumar, S. Anil; Krishnasastry, M. V.; Abyaneh, Majid Kazemian; Kulkarni, Sulabha K.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Biomedical Nanotechnology, 2007)
This paper presents the in vitro synthesis of CdS quantum dot nanoparticles using sulphite reductase and capping peptide in the presence of a co-factor alpha-NADPH, their characterization and conjugation with plant lectins, Jacalin and Chick pea lectin. Incubation of sulphite reductase with aqueous CdCl2, Na2SO3, and capping peptide in the presence of a-NADPH, which acts as a co-factor, resulted in the formation of CdS nanoparticles of dimensions 5-20 nm. These CdS nanoparticles were conjugated with plant lectins by EDAC mediated coupling. These observations are of significance, as it will help in the development of eco-friendly process for the formation of CdS nanoparticles and their application as fluorescent biolabels. Moreover the above studies will also help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: bio-label; CdS quantum dots; conjugation; Enzyme; in vitro synthesis; Nanoparticles

Chemical, thermal and pH-induced equilibrium unfolding studies of fusarium solani lectin - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The effect of urea, guanidine thiocyanate, temperature and pH was studied on the conformational stability of Fusarium solani lectin. Equilibrium unfolding with chemical denaturants showed that the lectin was least stable at pH 12 and maximally stable at pH 8.0 near its pI ( 8.7). Guanidine thiocyanate ( the concentration of denaturant at which the protein is half folded, D-1/2 = 0.49 M at pH 12) was found to be an eight times stronger denaturant than urea (D-1/2 = 3.88 M at pH 12). The unfolding curves obtained with fluorescence and CD measurements showed good agreement indicating a monophasic nature of unfolding and excluded the possibility of formation of any stable intermediate. The effect of pH on the lectin was found to be unusual as at acidic pH, the lectin showed a flexible tertiary structure with pronounced secondary structure, and retained its hemagglutinating activity. On the other hand, the lectin did not show any loss of conformation or activity upto 70 degrees C for 15 min. Moreover, thermal denaturation did not result in the aggregation or precipitation of the protein even at high temperatures. Thermal denaturation was also carried out in the presence of a low concentration of guanidine thiocyanate. Change in the enthalpy of transition (Delta H-m) varied linearly with transition temperature (T-m), which indicated that the heat capacity (Delta C-p =3.95 kJ (.) mol(-1) (.) K-1) of the lectin remained constant during the unfolding.
Keywords: Denaturation; Fusarium solani; guanidine; Lectin; thermal; Unfolding

Complex carbohydrate specificity of lectin from fruiting body of ganoderma lucidum. a surface plasmon resonance study - Thakur, Atul; Pal, Lakhan; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The thermodynamics and kinetics of binding of glycans and glycoproteins to Ganoderma lucidum lectin was studied using surface plasmon resonance. The lectin showed highest affinity for asialo triantennary N glycan (Ka = 3.52 x 10(5)) among the glycans tested. There was a several fold increase in affinity for glycoproteins compared to their corresponding glycans and coincident increase in contribution from enthalpy (Delta H), suggesting the involvement of hydrogen bonding in the interaction as well as involvement of protein-protein interactions. Increased affinity also showed increase in unfavorable negative binding entropy (Delta S) which was compensated with higher enthalpy. The glycoproteins showed faster association rates (k(1)) and the activation energy (E-1(double dagger)) in the association process was much lower for the glycoproteins than glycans, resulting in their faster associations. These observations elaborate the role of protein matrix in lectin-glycoconjugate interaction.
Keywords: ganoderma lucidum; glycans; Lectin; SPR

Nitrate reductase-mediated synthesis of silver nanoparticles from AgNO3 - Kumar, S. Anil; Abyaneh, Majid Kazemian; Gosavi, S. W.; Kulkarni, Sulabha K.; Pasricha, Renu; Ahmad, Absar; Khan, Mohammad Islam (Biotechnology Letters, 2007)
Synthesis of silver nanoparticles using alpha-NADPH-dependent nitrate reductase and phytochelatin in vitro has been demonstrated for the first time. The silver ions were reduced in the presence of nitrate reductase, leading to the formation of a stable silver hydrosol 10-25 nm diam. and stabilized by the capping peptide. The nanoparticles were characterized by X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and UV-Vis absorption. These studies will help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: Capping Peptide; enzymatic method; nitrate reductase; silver nanoparticles

Purification and characterization of a lectin from endophytic fungus fusarium solani having complex sugar specificity - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (Archives of Biochemistry and Biophysics, 2007)
A lectin from the mycelial extract of an endophytic strain of Fusarium solani was purified. Its hemagglutinating activity was inhibited by glycoproteins possessing N-linked as well as O-linked glycans. The thermodynamics and kinetics of binding of glycans and glycoproteins to F. solani lectin Was Studied using SUH ace plasmon resonance. The lectin showed high affinity for asialofetuin, asia-lofibrinogen, asialofibrinogen, and thyroglobulin: and comparatively low affinity for mucin, fetuin, fibrinogen, and holotransferrin. Glycoproteins showed glycans with significant contribution from enthalpy and positive entropy, suggesting several fold higher affinity than their corresponding g the involvement of non-polar protein-protein interaction. Moreover, the higher affinity of the glycoproteins was due to their faster association rates and low activation energy. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: endophytic fungus; Fusarium solani; Lectin; Purification; SPR; Thermodynamic properties

Synthesis and evaluation of 1-deoxy-8-epi-castanospermine, 1-deoxy-8-hydroxymethyl castanospermine, and (6S,7S,8R,8aR)-8-amino-octahydroindolizine-6,7-diol - Pandey, Ganesh; Dumbre, Shrinivas G.; Pal, Sujit; Khan, Mohammad Islam; Shabab, A. (Tetrahedron, 2007)
A short, versatile, and enantioselective synthesis of 1-deoxy-8-epi-castanospermine (5), 1-deoxy-8-hydroxymethyl castanospermine (6), and (6S,7S,8R,8aR)-8-amino-octahydroindolizine-6,7-diol (7) is achieved from a common template 12. The key step utilized is PET provoked amine radical cyclization of 11 to 12 in excellent diastereoselectivity. The exocyclic double bond at C-8 of the template is functionalized to obtain 5-7 as exclusive diastereomers. 1-Deoxy-8-epi-castanospermine exhibited inhibition of alpha- and beta-galactosidase and beta-glucosidase. Compounds 6 and 7 were found to be weak inhibitors of beta-glucosidase. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1-deoxy-8-epi-castanospermine; castanospermine; Glycosidase inhibitors

Antibacterial activity of synthesized 2,4,5-trisubstituted imidazole derivatives - Khan, Mohd Sajid; Siddiqui, Shafi Ahmad; Siddiqui, Mohammad Shaik Rafi Ahmad; Goswami, Usha; Srinivasan, Kumar Venkatraman; Khan, Mohammad Islam (Chemical Biology & Drug Design, 2008)
Some novel chemically synthesized 2,4,5-trisubstituted imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone were screened against eight different human pathogenic bacteria and fungi. Seven compounds were found to be active against different bacteria. These compounds showed variation in activity and were found to be active against Gram-positive as well as Gram-negative bacteria. Compound 4-(4,5-diphenyl-1H-imidazol-2-yl)-phenol, 3d was the only compound which showed activity against Klebsiella pneumoniae while rest of the compounds did not show significant activity against this micro-organism. Minimum inhibitory concentrations of the compounds were in the range of 0.50 to 6.1 mu g/mL and minimum bactericidal concentration ranges from 1.11 to 12.9 mu g/mL. The candidature of active compounds to be an effective and novel drug was examined based on Lipinski's rule of Five which explained ClogP, LogS, H-bond acceptors, H-Bond donors and rotational bonds. Compounds 3a-d and 3f satisfies Lipinski's rule of Five and could be proposed as potent new antibacterial drugs.
Keywords: 1; 2; 2-Diketones; 4; 5-trisubstituted imidazoles; alpha-hydroxyketone; antibacterial activity; aryl aldehydes

First asymmetric total synthesis of penarolide sulfate A(1) - Mohapatra, Debendra K.; Bhattasali, Debabrata; Gujar, Mukund K.; Khan, Mohammad Islam; Shashidhara, K. S. (European Journal of Organic Chemistry, 2008)
Penarolide sulfate A(1), with three contiguous stereogenic centers on a macrocyclic skeleton, affords promise as an alpha-glucosidase inhibitor. Herein, we describe the first asymmetric total synthesis of this natural product. A stereoselective strategy for rapid assembly of the complete framework of the 30-membered macrocyclic core is delineated herein. Sequential amidation and intramolecular Sonogashira cross-coupling reactions were pivotal to the success of our efforts. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Asymmetric synthesis; C-C coupling; Dihydroxylation; epoxidation; Macrocycles; Regioselectivity; Total synthesis

Purification and characterization of a T-antigen specific lectin from the coelomic fluid of a marine invertebrate, sea cucumber (Holothuria scabra) - Gowda, Nagaraj M.; Goswami, Usha; Khan, Mohammad Islam (Fish & Shellfish Immunology, 2008)
A novel lectin was purified from the coelomic fluid of the sea cucumber Holothuria scabra (HSL), subjected to bacterial challenge. HSL is a monomeric glycoprotein of molecular mass 182 kDa. The lectin is highly thermostable as it retains full activity for 1 h at 80 degrees C. Further, the hemagglutination activity of HSL is unaffected by pH in the range 2-11. Unlike other lectins purified from marine invertebrates, the hemagglutination activity of HSL does not require any divalent metal ions. The affinity profile of HSL was studied by a combination of hemagglutination inhibition and fluorescence spectroscopy. HSL binds to desialylated glycoproteins, Me alpha Gal, T-antigen and T (alpha-ser)-antigen with a distinction between beta 1-4 and beta 1-3 linkages. Me alpha-T-antigen was a potent ligand having highest affinity (K-a 8.32 x 10(7) M-1). Monosaccharide binding is enthalphically driven while disaccharide binding involves both entropic and enthalpic contributions. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Fluorescence spectroscopy; Holothuria scabra; Lectin; marine invertebrate; Thermodynamic properties

Serine protease inhibitor from hemolymph of green mussel, perna viridis - Khan, M. S.; Goswami, U.; Rojatkar, S. R.; Khan, Mohammad Islam (Bioorganic & Medicinal Chemistry Letters, 2008)
Bioactivity guided fractions of cell-free hemolymph of bacterially challenged marine mussel, Perna viridis led to the isolation of a novel quaternary alkaloid 1, which was identified by its spectral data. The isolated molecule 1 has been found to be a potent serine protease inhibitor ( SPI) showing IC(50) and K(i) values of 102.5 and 97.1-104.68 mu M, respectively. The E(t)/K(i) value of SPI is 6.3, whereas E(t)/K(m) value is 1.04. The Van't Hoff analysis showed that the value of K(i) decreases with increase in temperature, and the binding of the inhibitor is entropically driven. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: hemolymph; Natural product; Perna viridis; protease inhibitor

Steady state and time-resolved fluorescence studies of a hemagglutinin from Moringa oleifera - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (Journal of Fluorescence, 2008)
The saccharide binding and conformational characterization of a hemagglutinin, a low molecular weight protein from the seeds of Moringa oleifera was studied using steady state and time resolved fluorescence. The lectin binds sugars LacNAc (K-a = 1380 M-1) and fructose (K-a = 975 M-1), as determined by the fluorescence spectroscopy. It has a single tryptophan per monomer which is exposed on the surface and is in a strong electropositive environment as revealed by quenching with iodide. Quenching of the fluorescence by acrylamide involved both static (K-s = 0.216 M-1) and collisional (K-sv= 8.19 M-1) components. The native protein showed two different lifetimes, tau(1) (1.6 ns) and tau(2) (4.36 ns) which decrease and get converted into a single one, (2.21 ns) after quenching with 0.15 M acrylamide. The bimolecular quenching constant, k(q) was 7.55 x 10(11) M-1 s(-1). ANS binding studies showed that the native protein has exposed hydrophobic patches which get further exposed at extreme acidic or alkaline pH. However, they get buried in the interior of the protein in presence of 1 M GdnHCl or urea.
Keywords: ANS binding; fluorescence; Hemagglutinin; lifetime; Moringa oleifera; saccharide binding; Solute quenching

Structure-activity relationship of a hemagglutinin from Moringa oleifera seeds - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2008)
The hemagglutinin from the seeds of Moringa oleifera (MoL) agglutinates human as well as rabbit erythrocytes; the affinity for the latter is almost 250 times more than that for the former. MoL was inhibited by glycoproteins namely thyroglobulin, fetuin and holotransferin indicating the complex sugar specificity of the lectin. The protein is a homodimer with molecular mass of 14 kDa, subunits (7.1 kDa) linked by the disulfide bond(s). The secondary structure elements of MoL area-helix, 28%; beta-sheet, 23%; turn 20% and unordered 28%. While the activity and secondary structure were not affected at extreme pH and high temperature, they were drastically affected in presence of dithiothreitol at and above pH 7.0, indicating that disulfide linkages hold the active conformation of the protein. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: disulfide linkages; Moringa oleifera hemagglutinin; Secondary structure

Study of papain-cystatin interaction by intensity fading MALDI-TOF-MS - Shabab, M.; Kulkarni, Mahesh J.; Khan, Mohammad Islam (Protein Journal, 2008)
Intensity fading (IF) matrix assisted laser desorption ionization (MALDI) time of flight (TOF) mass spectrometry (MS ) has become an alternative screening approach for the affinity-binding analysis of proteins and peptides with molecular ligands. In this investigation an attempt has been made to study the protein ligand interaction by intensity fading (IF) MALDI-MS using papain and cystatin as model system for protein-ligand interactions. The intensity fading of cystatin was monitored using various concentration of cystatin ranging from (1 to 8.6 mu M) in presence of target protein, papain. The results indeed indicate that the intensity of cystatin decreases upon addition of papain. Furthermore, for the first time we have used IF-MALDI-MS for determining the number of binding sites for cystatin on papain by Scatchard analysis.
Keywords: intensity fading; MALDI; papain-cystatin; protein-ligand interaction; Scatchard plot

Synthesis of polyhydroxy piperidines and their analogues: a novel approach towards selective inhibitors of alpha-glucosidase - Pandey, Ganesh; Bharadwaj, Kishor Chandra; Khan, Mohammad Islam; Shashidhara, K. S.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2008)
Various polyhydroxy piperidine azasugars have been synthesized from precursors 18a and 18b, obtained in both enantiomeric forms from D-ribose. Out of these polyhydroxy piperidine azasugars, 22, 39 and 20 were found to be potent as well as selective inhibitors of a-glucosidase with K(i) values ranging as low as 1.07 mu M, 16.4 mu M, and 88.2 mu M, respectively. Replacement of the hydroxy methylene moiety of 19 (K(i) 33% at 1 mM) by an amino methylene moiety (32, K(i) 36.8 mu M) showed a remarkable increase in the activity (almost 30 times). Furthermore, increasing the lipophilicity of 33 by N-alkylation with a dodecyl group (36) showed a three-fold enhancement in the activity (K(i) 217 mu M to K(i) 72.3 mu M).

T-antigen binding lectin with antibacterial activity from marine invertebrate, sea cucumber (Holothuria scabra): possible involvement in differential recognition of bacteria - Gowda, Nagaraj M.; Goswami, Usha; Khan, Mohammad Islam (Journal of Invertebrate Pathology, 2008)
In invertebrates, cellular and humoral components are evolved to maintain their body immunity and integrity. Both these factors respond to different antigens such as microorganisms, vertebrate erythrocytes and foreign proteins. In this article, we report a study of a lectin (HSL) involved in immune response in the echinoderm, sea Cucumber (Holothuria scabra). Correlative studies indicate that the expression of this defensive lectin is induced by bacterial challenge, wherein cell wall glycoconjugates of bacteria are involved in lectin induction. HSL showed strong broad spectrum antibacterial activity against both gram-positive and gram-negative bacteria. Under in vitro conditions, purified HSL mediate agglutination of the test bacteria, there by indicating a possible mode of action in physiological situation. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: agglutination; antibacterial activity; coelomic fluid; Holothuria scabra; Lectin; sea cucumber

Taxol and 10-deacetylbaccatinIII induce distinct changes in the dynamics of caveolae - Ahmed, Neesar; Dasari, Sreekanth; Srivastava, Saumya S.; Sneh, Amita; Ahmad, Absar; Khan, Mohammad Islam; Krishnasastry, M. V. (FEBS Letters, 2008)
Taxol treatment of HeLa cells resulted in a transient recruitment of Caveolin-1 to the cell surface followed by internalization. Interestingly, 20 min after 10-deacetylbaccatinIII (10-DAB) treatment, the caveolae displayed faster `kiss and run' dynamics while BaccatinIII (BacIII) did not induce any change. Sustained phosphorylation of Caveolin-1 is observed upon treatment and between Taxol and 10-DAB, the former shows phosphorylated Raf-1, ERK1/2 and hyperphosphorylated Bcl-2 while the later showed much less magnitude of the same. BacIII treatment did not induce phosphorylation of Raf-1 or Bcl-2. It is possible that Taxol might act on multiple targets and the side chain may be crucial. (c) 2008 Federation of European Biochemical Societies. Published by Elsevier B. V. All rights reserved.
Keywords: 10-DeacetylbaccatinIII; BaccatinIII; Caveolae; Cytotoxicity; Kiss and run dynamic; Taxol; TIRFM

Click chemistry based rapid one-pot synthesis and evaluation for protease inhibition of new tetracyclic triazole fused benzodiazepine derivatives - Mohapatra, Debendra K.; Maity, Pradip K.; Shabab, M.; Khan, Mohammad Islam (Bioorganic & Medicinal Chemistry Letters, 2009)
We describe herein a one-pot synthesis of novel tetracyclic scaffolds that incorporate a fusion of a proline, 1,2,3-triazole ring with [1,4]-benzodiazepin-8(4H)-one ring systems following click chemistry. The expected peptide bond formation followed by in situ 1,3-dipolar cycloaddition in absence of any catalyst led to the formation of new triazole fused benzodiazepine derivatives. (C) 2009 Published by Elsevier Ltd.

Comparative studies of two araceous lectins by steady state and time-resolved fluorescence and CD spectroscopy - Dharker, Poorva N.; Gaikwad, Sushama M.; Suresh, C. G.; Dhuna, Vikram; Khan, Mohammad Islam; Singh, Jatinder; Kamboj, Sukhdev Singh (Journal of Fluorescence, 2009)
Transitions in the tryptophan microenvironment and secondary structure of two monocot lectins from Sauromatum guttatum and Arisaema tortuosum under different denaturing conditions were studied by steady state and time resolved fluorescence and CD spectroscopy. The lectins exist as tetramers with a single tryptophan residue estimated per monomer, present in a polar environment. Quenching with ionic quenchers showed predominantly electropositive environment for tryptophan residues. Acrylamide had maximum quenching effect. A decrease in KI quenching due to lectin denaturation indicated redistribution of charges as a result of possible conformational change. The two values for lifetimes of tryptophanyl population (1.2-1.4 and 6.3-6.4 ns) reduced substantially on quenching or denaturation. Similarly, both the lectins showed a drastic loss of secondary structure in 5 M Gdn-HCl or 6 M Urea or at pH 2.0 and below. For the first time araceous lectins, like legume lectins are shown to bind adenine. The presence of a compact structure at alkaline pH 10.0-12.0 was observed in CD spectra.
Keywords: Araceae lectins; Denaturation; fluorescence; Lifetime spectroscopy; Secondary structure

Interaction of alpha-mannosidase from aspergillus fischeri with glycosidase inhibitors, metal ions and group specific reagents - Shashidhara, K. S.; Gaikwad, S. M.; Khan, Mohammad Islam; Bharadwaj, Kishor Chandra; Pandey, G. (Research Journal of Biotechnology, 2009)
As an initial step towards using alpha-mannosidase as a target against anticancer drugs, inhibition studies of a model enzyme, class II alpha-mannosidase from Aspergillus fischeri in presence of polyhydroxy piperidine derived glycosidase inhibitors, metal ions and amino acid specific reagents were carried out to reveal the sensitivity of the enzyme. Three of the derivatives (Compound 20, 32 and 39)(11) showed competitive inhibition (K(i) =45, 48 and 235 mu M) and the binding of the inhibitors to the enzyme was entropically driven. Among the metal ions checked, Cu(++) (K(i) = 21nm) and Se(++) ions (K(i) = 32 mu M) showed noncompetitive and Co(++) (K(i) = 1.195 mM) showed competitive inhibition of the enzyme activity with insignificant change in the secondary structure of the protein. The above studies exhibit the Potential of the enzyme in studying anticancer drugs. Treatment of the enzyme with group specific reagents showed the presence of carboxylate, Arg and Cys at the active site. Substrate protection studies and kinetics of the modified enzyme confirmed the above results. Trp and His at the active site were observed to be in proximity.
Keywords: active-site; alpha-Mannosidase; Chemical modification; Glycosidase inhibitors; metal ions

Production, purification, and characterization of taxol and 10-DABIII from a new endophytic fungus gliocladium sp isolated from the Indian yew tree, taxus baccata - Sreekanth, D.; Syed, A.; Sarkar, S.; Sarkar, Dhiman; Santhakumari, B.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Microbiology and Biotechnology, 2009)
We have isolated endophytic fungi from the Indian yew tree, Taxus baccata, and then screened for taxol production. Out of the 40 fungal cultures screened, one fungus Gliocladium sp. was found to produce taxol and 10-DABIII (10-deacetyl baccatin III). These compounds were purified by TLC and HPLC and characterized using UV-spectroscopy, ESI-MS, MS/MS, and proton NMR. One liter of Gliocladium sp. culture yielded 10 mu g of taxol and 65 mu g of 10-DABIII. The purified taxol from the fungus showed cytotoxicity towards cancer lines HL-60 (leukemia), A431 (epidermal carcinoma), and MCF-7 (breast cancer).
Keywords: 10 DAB III; Endophytic fungi; Gliocladium sp.; Taxol; Taxus baccata

Purification and characterization of putative alkaline [Ni-Fe] hydrogenase from unicellular marine green alga, tetraselmis kochinensis NCIM 1605 - Bhosale, Siddharth H.; Pant, A.; Khan, Mohammad Islam (Microbiological Research, 2009)
Hydrogenase enzyme from the unicellular marine green alga Tetraselmis kochinensis NCIM 1605 was purified 467 fold to homogeneity. The molecular weight was estimated to be similar to 89kDa by SDS-PAGE. This enzyme consists of two subunits with molecular masses of similar to 70 and similar to 19 kDa. The hydrogenase was found to contain 10 g atoms of Fe and 1 g of atom of Ni per mote of protein. The specific activity of hydrogen evolution was 50 mu mol H-2/mg/h of enzyme using reduced methyl viologen as an electron donor. This hydrogenase enzyme has pl value similar to 9.6 representing its alkaline nature. The absorption spectrum of the hydrogenase enzyme showed an absorption peak at 425 nm indicating that the enzyme had iron-sulfur clusters. The total of 16 cysteine residues were found per mote of enzyme under the denaturing condition and 20 cysteine residues in reduced denatured enzyme indicating that it has two disulfide bridges. (C) 2007 Published by Elsevier GmbH.
Keywords: Characterization; Chemical modification; Ni-Fe hydrogenase; Tetraselmis kochinensis; Unicellular green algae

Synthesis of polyfunctional quinolizidine alkaloids: development towards selective glycosidase inhibitors - Pandey, Ganesh; Grahacharya, Debasish; Shashidhara, K. S.; Khan, Mohammad Islam; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2009)
A highly divergent route to a variety of quinolizidine alkaloids is described. The enantiomeric precursors 22a and 22b utilized for the synthesis of these alkaloids were constructed stereospecifically from the PET cyclization of the corresponding acetylene tethered alpha-trimethylsilyl amine moieties 21a and 21b, respectively, both of which were synthesised from D-ribose. The polyhydroxy quinolizidine alkaloid 7 was found to be a selective inhibitor of alpha-galactosidase with Ki 83.9 mu M. The amine analogs 18, 12 and 10 are found to be selective and potent inhibitors of alpha-glucosidase with Ki 28, 120 and 140 mu M, respectively.

Heterofunctional nanomaterials: fabrication, properties and applications in nanobiotechnology - Kumar, S. Anil; Khan, Mohammad Islam (Journal of Nanoscience and Nanotechnology, 2010)
Nanotechnology and nanoengineering includes a novel class of materials that are gaining significant recognition to pursuit technological/biological advances in diverse fields including, biology, medicine, electronics, engineering etc. due to their unique size- and shape-dependent intrinsic physicochemical, optoelectronic and biological properties. Characteristics such as high surface to volume ratios and quantum confinement results in materials that are qualitatively different from their bulk counterparts. These properties not only make them suitable for numerous applications in existing and emerging technologies, but also have outstanding role in many fields that provide inspiration for their fabrication. In Today's trend nanotechnology is spreading vigorously where researchers all over the world are focusing towards their synthesis and applications. Therefore, this review is helpful for the researchers in the field of nanobiotechnology/nanomedicine, providing a brief overview of nanotechnology, covering nanomaterial synthesis methods (with emphasis on environmentally benign greener approaches), their properties, and applications; such as drug delivery, bio-labeling, nanotoxicity etc. The influence of synthesis methods and surface coatings/stabilizing agents and their subsequent applications is discussed, and a broad outline on the biomedical applications into which they have been implemented is also presented.
Keywords: Bio-Fabrication; Bio-Labeling; Cell imaging; drug delivery; Greener Synthesis; Nanomaterials; Nanotoxicity

Isolation, structure, and functional elucidation of a modified pentapeptide, cysteine protease inhibitor (CPI-2081) from streptomyces species 2081 that exhibit inhibitory effect on cancer cell migration - Singh, Jay Prakash; Tamang, Sudarsan; Rajamohanan, P. R.; Jima, N. C.; Chakraborty, Goutam; Kundu, Gopal C.; Gaikwad, Sushama M.; Khan, Mohammad Islam (Journal of Medicinal Chemistry, 2010)
Cysteine proteases play an important role in cell migration and tumor metastasis. Therefore, their inhibitors are of colossal interest, having potential to be developed as effective antimetastatic drugs for tumor chemotherapy. Traditionally, secondary metabolites from streptomyces show a wide range of diversity with respect to their biological activity and chemical nature. In this article, we have described the characterization of small molecule cysteine protease inhibitor, CPI-2081 (compound 1), a mixture of two novel pentapeptides, compound 1a (736.71 Da), and compound 1b (842.78 Da), isolated from Streptomyces species NCIM2081, following solvent extraction and repeated HPLC based on C18 chemistry, and completely characterized using a variety of both ID and 2D NMR spectroscopy. Further, it was found that nanomolar concentration of compound 1 is able to inhibit papain hydrolytic activity. Also, compound 1 significantly inhibits tumor cell migration at sub cytotoxic concentration, indicating its remarkable potential to be developed as antimetastatic drug, which will make chemotherapy more localized and specific, thereby minimizing the hazardous side effects on normal tissues.

Steady state and time resolved fluorescence quenching and chemical modification studies of a lectin from endophytic fungus fusarium solani - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (Journal of Fluorescence, 2010)
The solute quenching studies of a lectin from endophytic fungus Fusarium solani were carried out using different quenchers such as acrylamide, succinimide, potassium iodide and cesium chloride. The lectin showed emission maximum at 348 nm indicating relative exposure of tryptophan. The quenchable fraction of the fluorophore was 100% with acrylamide, whereas it was only 50% with succinimide. The ionic quenchers iodide and cesium showed opposite effects at different pH. In the case of cesium, raising the pH resulted in increased quenching and accessibility of typtophan residue, while the iodide showed just opposite effect. These studies showed that the single tryptophan residue of the lectin (per monomer) is relatively exposed, and might be in the vicinity of positively charged amino acid residues. Various amino acids of the F. solani lectin were modified using different reagents to obtain information about the hemagglutinating site. The chemical modification studies suggested tyrosine residues can be modified using N-acetylimidazole, which results in complete loss of hemagglutination activity of the lectin. Kinetics of chemical modification suggested involvement of only 2 tyrosine residues. Modification of arginine, cysteine, histidine, lysine, aspartate, glutamate and tryptophan did not result in loss of hemagglutinating activity of the lectin.
Keywords: Chemical modification; fluorescence; Fusarium; Lectin; Quenching; Time-resolved

Carbon nanotube-modified sodium dodecyl sulfate-polyacrylamide gel electrophoresis for molecular weight determination of proteins - Parthasarathy, Meera; Debgupta, Joyashish; Kakade, Bhalchandra A.; Ansary, Abu Ayoobul; Khan, Mohammad Islam; Pillai, Vijayamohanan K. (Analytical Biochemistry, 2011)
The effect of incorporating carbon nanotubes (CNTs) in the gel matrix on the electrophoretic mobility of proteins based on their molecular weight differences was investigated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). More specifically, a reduction in standard deviation in the molecular weight calibration plots by 55% in the case of multiwalled carbon nanotubes (MWCNTs) and by 34% in the case of single-walled carbon nanotubes (SWCNTs) compared with that of pristine polyacrylamide gels was achieved after incorporating an insignificant amount of functionalized CNTs into the gel matrix. A mechanism based on a more uniform pore size distribution in CNT modified polyacrylamide gel matrix is proposed. Furthermore, the impact of SWCNTs and MWCNTs on the mobility of proteins in different molecular weight regimes at a given acrylamide concentration offers a tunable gel matrix in terms of the selection of molecular weight ranges of proteins. The robustness and excellent reproducibility of the CNT-PAGE protocol are expected to have a significant impact on the molecular weight determination of newly isolated proteins. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Carbon nanotubes; Gel electrophoresis; Molecular weight determination; Polyacrylamide; Protein separation

Efficient synthesis of benzodiazepinyl phosphonates as clostripain inhibitors via FeCl3 catalyzed four-component reaction - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Raut, Dnyaneshwar S.; Mhaindarkar, Vaibhav P.; Khan, Mohammad Islam (Organic & Biomolecular Chemistry, 2011)
A novel one-pot route for the synthesis of benzodiazepinyl phosphonates (BDPs) has been achieved. FeCl3 efficiently catalyzed four-component condensation of diamines, acetone and phosphites in the presence of molecular sieves to furnish BDPs as novel chemical entities with good yield. The synthesized BDPs have shown significant protease inhibition activity against clostripain, a disease model for gas gangrene, suggesting that these novel chemical entities could be further explored as cysteine protease inhibitors.

Kinetics and thermodynamics of glycans and glycoproteins binding to holothuria scabra lectin: a fluorescence and surface plasmon resonance spectroscopic study - Gowda, Nagaraj M.; Gaikwad, Sushama M.; Khan, Mohammad Islam (Journal of Fluorescence, 2013)
Holothuria scabra produces a monomeric lectin (HSL) of 182 kDa. HSL showed strong antibacterial activity and induced bacterial agglutination under in vitro conditions, indicating its role in animals' innate immune responses. Very few lectins have been reported from echinoderms and none of these lectins have been explored in detail for their sugar-binding kinetics. Affinity, kinetics and thermodynamic analysis of glycans and glycoproteins binding to HSL were studied by fluorescence and surface plasmon resonance spectroscopy. Lectin binds with higher affinity to O-linked than N-linked asialo glycans, and the affinities were relatively higher than that for sialated glycans and glycoproteins. T-antigen alpha-methyl glycoside was the most potent ligand having the highest affinity (Ka 8.32 x10(7) M-1). Thermodynamic and kinetic analysis indicated that the binding of galactosyl Tn-antigen and asialo glycans is accompanied by an enthalpic contribution in addition to higher association rate coupled by low activation energy for the association process. Presence of sialic acid or protein matrix inhibits binding. Higher affinity of HSL for O-glycans than N-glycans had biological implications; since HSL specifically recognizes bacteria, which have mucin or O-glycan cognate on their cell surfaces and play a major role in animal innate immunity. Since, HSL had higher affinity to T-antigen, makes it a useful tool for cancer diagnostic purpose.
Keywords: Holothuria scabra; Kinetic analysis; Lectin; Surface plasmon resonance spectroscopy; Thermodynamic properties

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles